Fifteen-minute consultation: incidental findings on brain and spine imaging. Issue 6 (22nd August 2014) - Patel, Chirag; Rodrigues, Desiderio
Abstract : Incidental findings on imaging of the brain and spine account for a large number of referrals to a paediatric neurosurgical practice. They can be cause of undue concern to the parents and can result in unnecessary investigations and interventions. This article is a review of the common pathological entities identified as incidental findings in the author's experience. The list is not exhaustive and reflects mainly the common conditions referred. Very few of these incidental findings would need surgical intervention.